Towards an Inclusive Creative Economy: Applying John Rawls’ Economic Justice to Empower Reog Ponorogo Artists - Damanuri, Aji; Futaqi, Faruq Ahmad (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2025)
Reog Ponorogo, a traditional Indonesian art form, plays a significant role in shaping the creative economy and cultural identity of the Ponorogo Regency. Despite their cultural importance and economic potential, the distribution of economic benefits among stakeholders remains unequal, leaving many artists economically vulnerable. This study explores the application of John Rawls’s principles of economic justice to address income disparities and foster an inclusive creative economy in the Reog Ponorogo ecosystem. Through a qualitative phenomenological approach, this research examines the lives of art actors and stakeholders, as well as the creative economic empowerment strategies implemented by the local government. The findings reveal a significant income gap between performers, who earn a modest income of 50,000–300,000 rupiah per performance, and entrepreneurs dealing with Reog attributes and souvenirs, who can generate a turnover of up to 100 million rupiah per month. Applying Rawls' principles of equal basic freedom and the difference principle, this study proposes policy recommendations and strategies to ensure fair access to opportunities, the equitable distribution of income, education and capacity building, market expansion, and policy support. By aligning these elements with Rawls' principles, the creative economy can celebrate cultural heritage, while promoting economic growth and social equality. This study bridges the gaps in the existing literature by integrating cultural preservation with economic empowerment, offering valuable insights for policymakers, cultural practitioners, and scholars in fostering an inclusive and sustainable creative economy.